Therapeutic Hypothermia and Cell Therapy Change Cognitive Functions of Spontaneously Hypertensive Rats - Kudokotseva, Olga; Lomakin, Ivan; Babiichuk, Vladyslav; Babiichuk, Liudmyla; Kandybko, Igor (Problems of Cryobiology and Cryomedicine, 2023)
The paper presents the research results of spatial memory and learning processes for the comprehensive analysis of cognitive function of spontaneously hypertensive rats under the influence of independent and combined use of rhythmic craniocerebral hypothermia (RCH) and the introduction of cryopreserved cord blood nucleated cells (cCBNCs). It was shown that SHR rats have a cognitive deficit, which is manifested in reduced speed of the learning process and memory formation in the Morris water maze (MWM). The administration of therapeutic RCH and/or cell therapy (cCBNCs introduction) 30 days before training in the MWM improved the cognitive functions of SHR rats: the target search strategy changed, and the time to search for a platform hidden under water was significantly reduced. These changes indicated the acceleration of the processes of information perception, learning, and the formation of spatial memory. The preservation and reproduction of long-term memory and as a result of the formed strategy of direct finding of the target in the MWM was most influenced by certain therapy with the samples of cryopreserved cord blood in combination with the procedure of therapeutic hypothermia. It was established that this approach exerted a neuroprotective effect, contributing to the partial elimination of cognitive deficits in SHR by improving spatial memory and accelerating learning processes. Probl Cryobiol Cryomed 2023; 33(3): 201–211